Use of the ReCIVA device in breath sampling of patients with acute breathlessness: a feasibility study. Issue 4 (23rd November 2020) - Holden, Karl A.; Ibrahim, Wadah; Salman, Dahlia; Cordell, Rebecca; McNally, Teresa; Patel, Bharti; Phillips, Rachael; Beardsmore, Caroline; Wilde, Michael; Bryant, Luke; Singapuri, Amisha; Monks, Paul; et al.
Introduction: Investigating acute multifactorial undifferentiated breathlessness and understanding the driving inflammatory processes can be technically challenging in both adults and children. Being able to validate noninvasive methods such as breath analysis would be a huge clinical advance. The ReCIVA® device allows breath samples to be collected directly onto sorbent tubes at the bedside for analysis of exhaled volatile organic compounds (eVOCs). We aimed to assess the feasibility of using this device in acutely breathless patients. Methods: Adults hospitalised with acute breathlessness and children aged 5–16 years with acute asthma or chronic stable asthma, as well as healthy adult and child volunteers, were recruited. Breath samples were collected onto sorbent tubes using the ReCIVA® device and sent for analysis by means of two-dimensional gas chromatography-mass spectrometry (GCxGC-MS). The NASA Task Load Index (NASA-TLX) was used to assess the perceived task workload of undertaking sampling from the patient's perspective. Results: Data were available for 65 adults and 61 children recruited. In total, 98.4% of adults and 75.4% of children were able to provide the full target breath sample using the ReCIVA® device. NASA-TLX measurements were available in the adult population with mean values of 3.37 for effort, 2.34 for frustration, 3.8 for mental demand, 2.8 for performance, 3.9 for physical demand and 2.8 for temporal demand. Discussion: This feasibility study demonstrates it is possible and acceptable to collect breath samples from both adults and children at the bedside for breathomics analysis using the ReCIVA® device. It is feasible to collect breath samples for breath analysis at the bedside using the ReCIVA device in acutely breathless adults and children https://bit.ly/2ZTonWo